Determining multi‐pesticide residues in teas by dispersive solid‐phase extraction combined with speed‐regulated directly suspended droplet microextraction followed by gas chromatography–tandem mass spectrometry. Issue 2 (5th November 2019) - Li, Jianxun; Shan, Jihao; Kong, Zhiqiang; Fan, Chunlin; Zhang, Zijuan; Fan, Bei
Abstract: In this study, an effective speed‐regulated directly suspended droplet microextraction method was developed to condense pesticide residues from teas through dispersive solid‐phase extraction prior to analysis by gas chromatography with tandem mass spectrometry. The extractant was intentionally dispersed into the sample solution in the form of globules through high‐speed agitation. This procedure increases the contact area between the binary phases and shortens the distribution equilibrium time. The fine globules reassembled by decelerating stirring speed, the extractant could be taken out for gas chromatography with tandem mass spectrometry. Recovery studies were performed under optimized extraction conditions by using matrix blanks fortified with pesticides at three concentrations (10, 50, and 100 µg/kg). Over 87% of the recoveries for the analytes in four tea matrices were acceptable given their recovery ranges of 70–120% and relative standard deviations of ≤20%. The limits of quantification of most pesticides were lower than 10 µg/kg and thus satisfied the requirements for maximum residue levels prescribed by the European Community. A total of 38 tea samples from local markets were analyzed by using the proposed method. Results showed that chlorpyrifos was the most frequently detected pesticide in teas. The method is a potential choice for the routine monitoring of pesticide residues in complex matrices.